Adhesion of biological membranes - Sengupta, Kheya; Smith, Ana-Suncana (Springer International Publishing, 2018)
One of the most important triggers of cell activity is adhesion, a process by which cells and their organelles interact and attach to substrates, internal scaffolds, external interfaces, or other cells. The physiological and pathological significance of cell adhesion is hard to exaggerate, and adhesion is ubiquitous in the living world. Adhesive contacts need to be able to function in widely varying circumstances and must be established in an extremely noisy environment. For these reasons, the control mechanisms of adhesion have had to develop so as to be able to permanently monitor and correct cellular performance. While a lot of effort has been invested into understanding the biochemical aspect of these processes, the underlying physical principles of adhesion regulation have obtained significantly less appreciation. Only in recent years have these two approaches begun to converge in a unified view. Due to the strong coupling of the biochemical reactions to the spatial coordination provided by membranes and the cytoskeleton, biological signaling is subject to a plethora of physical constraints. Indeed, many signaling pathways, particularly those involving the adhesion, involve protein diffusion and aggregation guided by membranes. It is these aspects of adhesion that can be understood in the framework of statistical physics, as we intend to demonstrate in this short review. Here we summarize the developments in understanding cell and membrane adhesion from a theoretical point of view and support it with experiments in model systems as well as with living cells.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Artificial cell; Cell adhesion; Competitive binding; Ligand-receptor interactions; Multiscale approaches to adhesion